Is the concept of mammalian epigenetic clocks universal and applicable to invertebrates? - Maleszka, Ryszard (Frontiers in Genetics, 2025)
Certain aspects of animal ageing can be quantified using molecular clocks or machine learning algorithms that are trained on specific omics data, with epigenetic clocks based on DNA methylation (DNAm) garnering the most attention. While the accuracy of epigenetic clocks has been established in mammals and several vertebrates, their applicability to invertebrates, which comprise 97% of all animal species, remains largely theoretical. In this context, we consider whether the relationship between chronological clocks, biological clocks, and DNA methylation is ancestral and evolutionarily conserved, potentially making it relevant beyond the vertebrate lineage. Evolutionary comparisons may help us determine whether epigenetic clocks are inherent mechanisms implemented during ageing or simply reflect the progressive erosion of epigenomic marks. These comparisons could also reveal the likely generality of the results from one type of epigenetic clock to another. We emphasise the substantial biological differences between invertebrates and mammals, all of which must be considered when evaluating the universality of epigenetic clocks. We conclude that mammalian-style DNAm epigenetic clocks are unlikely to be applicable to most invertebrates. We propose that quantitative approaches to ageing in non-vertebrate organisms should be specifically tailored to leverage the molecular mechanisms and distinct biology of different lineages.